Valorización económica, costos y tarifas del agua - Perez Grandez, Fernando (2011)
The broad consensus on the effective management of water resources is related to the consideration of water as an economic resource, as argued in the Document of the Intemational Conference on Water and environment, which states that" water has value economic development in all its competing uses and should be recognized as an economic good" is because water is a finite resource and must be recoverable and allocated according to criteria of efficiency and equity, ie the water in addition to being an economic good is also a social and environmental. The valuation of water, useful and have implications for policy on water resource management, and recognition of activities in which the value of water is high or low? and the factor and characteristics of the uses for that water is used. There is currently a discussion between the importance of the value of water and water costs, the value of water is not necessarily the cost of water. There are cultural, moral and religious, which we can not price for water is similar. Although it is expected to charge for water will be the primary way to incorporate the private sector, will continue to require public funding for a series of public good aspects of water resources. The determination of the water tariff should necessarily be based on economic principies of efficiency, equity and sustainability, whereas the concept of equity is taken into account only as a mechanism to control the rate. In that sense, the total amount paid by water users in an activity should not be greater than 3% of average monthly income of economic activity derived from the ENAHO. In addition to the Human Development Report (2006) of UNDP said that to meet the Millennium Development Goals Govemments should ensure that no household has to spend more than 3% of their income to meet their water needs, ensuring that no one denied access due to poverty. Finally, SUNASS from 2007, a systemic approach to watershed as a sustainable model for the supply of drinking water also establishes the definition of sustainable rates, the same that engages the user in the conservation of water sources and sinks and the strategy of compensation for ecosystem services.